If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + -1(9y + 2) = 5(y + -6) + 10 Reorder the terms: 13y + -1(2 + 9y) = 5(y + -6) + 10 13y + (2 * -1 + 9y * -1) = 5(y + -6) + 10 13y + (-2 + -9y) = 5(y + -6) + 10 Reorder the terms: -2 + 13y + -9y = 5(y + -6) + 10 Combine like terms: 13y + -9y = 4y -2 + 4y = 5(y + -6) + 10 Reorder the terms: -2 + 4y = 5(-6 + y) + 10 -2 + 4y = (-6 * 5 + y * 5) + 10 -2 + 4y = (-30 + 5y) + 10 Reorder the terms: -2 + 4y = -30 + 10 + 5y Combine like terms: -30 + 10 = -20 -2 + 4y = -20 + 5y Solving -2 + 4y = -20 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -2 + 4y + -5y = -20 + 5y + -5y Combine like terms: 4y + -5y = -1y -2 + -1y = -20 + 5y + -5y Combine like terms: 5y + -5y = 0 -2 + -1y = -20 + 0 -2 + -1y = -20 Add '2' to each side of the equation. -2 + 2 + -1y = -20 + 2 Combine like terms: -2 + 2 = 0 0 + -1y = -20 + 2 -1y = -20 + 2 Combine like terms: -20 + 2 = -18 -1y = -18 Divide each side by '-1'. y = 18 Simplifying y = 18
| 10x^4+4x^3= | | 12x^2-40x-32=0 | | 3x/2+7=x/3+10 | | 4(4x+40)=6(2x+60) | | 7+5x=-38 | | (x^2-3)(3x^3+375)(x^2+1)=0 | | s+5s=78 | | 4w^2+4w+1=121 | | 3+7x=33 | | 4x-8=x+7 | | 15z^2+7=20z-3 | | 3a^2-21-1=0 | | (x+35)+(x-5)+1.4x+x=360 | | n+32+n=126 | | 3x^2-9x-10=0 | | 8(x+2)-3(x-4)=6(x-7)+8 | | 3y^2-2=o | | X^2-5=4x^2-9x-5 | | 3x-4-5x=3x-2 | | 3y^2=16y-5 | | 3t+8(2+6)=2+14t | | 5x+(-19)=20+(-8x) | | 17m+26=-42 | | 1000=-16ft^2+1800 | | 14=3x(x-2)+5 | | 343+m^3= | | 5x+(-19)=20+(-8) | | 3(5-10)=36 | | 8n+(8n*2-6)=34 | | 7-9=y-4 | | 9z+12=6z+(-30) | | 2.6v=-20.8 |